Relevansi Filsafat Ilmu, Metode Ilmiah Dan Publikasi Ilmiah - Event, Diana; Heviana, Elsi; Rahayu, Ivo gana; Aiga, Ruspel; Ardime, Ardime (Peneliti.net, 2025)
Philosophy of Science is a special branch of Philosophy which has a strategic position in building the science paradigm in Indonesia. This research will examine and describe the status and position of Philosophy in the developing scientific paradigm. The research method used is a qualitative approach by analyzing sources or data from textbooks, scientific journals, documents, syllabi and teaching materials in Philosophy of Science lectures. The analysis used is interpretation, heuristics, and philosophical reflection. Scientific publication is a publication system that involves review by peer reviewers or colleagues with the aim of achieving the maximum level of objectivity. These “systems” vary depending on the discipline and continue to undergo evolution, although often with slow changes. The majority of academic works are published in scientific journals or in book form. The results of this research show that the Philosophy of Science was developed and taught referring to the philosophy of science paradigm that developed in the West. The structure built in developing the Philosophy of Science emerged from the study of Philosophy starting from basic knowledge about Philosophy to the nature of science.